Impact of social media strategies on stock price: the case of Twitter. (9th July 2018) - Chahine, Salim; Malhotra, Naresh K.
Abstract : Purpose: Social media have recently become an important strategic marketing tool to increase firm value. Based on an integrated theoretical framework, this study aims to examine the market reaction at the time of the creation of a Twitter platform for 312 firms from the Fortune 500 firms. Design/methodology/approach: To test the hypotheses related to the effect of social media platforms on firm value, the event history analysis (EHA) was used, also known as event study, usually designed to examine the impact of a historical phenomenon for the US Fortune 500 firms that developed a Twitter platform. Findings: A significant market reaction was found around the starting date of Twitter activities for the subsample of firms that are not contaminated by any other corporate announcements, but not for the overall sample. The market reaction is higher for firms with two-way interaction strategies rather than one-way messaging in both the uncontaminated subsample and the overall sample. It is higher in smaller firms, firms with losses and those with a family and/or a dominant shareholder. Further, firms in the contaminated subsample are likely to follow a two-way strategy after a positive revision of their earnings per share. We have run several robustness checks, including cross-validation on a holdout sample, and these findings remain consistent. Research limitations/implications: The integrated theoretical framework is another significant contribution. To our knowledge, this is the first study across disciplines that integrates the social exchange theory (SET), social representation theory (SRT), social network analysis (SNA), social identity theory (SIT), signaling theory (ST) and the impression management theory (IMT) into one framework that is built around information as a resource and social interaction. Practical implications: The results suggest that Twitter can be used to add value if firms interact and reciprocate with the various stakeholders. Social implications: Firms using social media must interact and reciprocate with the various stakeholders. Originality/value: This research is different than the published research on this topic in that it examines the impact on stock prices of the introduction of a specific social media platform, i.e. Twitter. The present results of the paper add to the prior research on database marketing and show that marketing "with" the customer is adding more value than marketing "to" the customer. The use of the net extends the scope of database marketing into a certain form of interaction marketing with "face-to-face" interaction within the relationships between the firm and its customers. Finally, the conditions under which social media platforms are used in an interactive manner are shown, and depicts that firms are more likely to use a two-way interactive strategy following a one-year period of positive momentum.